(untitled) (Marketing Journal, 2025)
This article analyzes the theoretical and practical foundations for the development of alternative types of tourism in Uzbekistan. Alongside traditional forms of tourism, the necessity of developing alternative directions that offer new experiences to both domestic and international tourists is substantiated. The study pays particular attention to the following types of tourism: public administration tourism, scientific tourism, geological (geo -) tourism, industrial tourism, and military tourism. For each o f these directions, the research examines international experiences, existing infrastructure, socio -economic conditions, and the practical possibilities of their implementation. According to the research findings, the development of these tourism types in Uzbekistan can serve as a significant factor in increasing tourist flows, reducing tourism seasonality, and creating new economic opportunities. At the same time, the study concludes that a separate strategic approach and government policy are necessary for each type of tourism.